Soil variability in La Violada Irrigation District (Spain): II Characterizing hydrologic and salinity features - Isidoro, D. (2020)
This paper focuses in analyzing the soil hydrologic features in La Violada Irrigation District (VID; a 5234 ha semi-arid irrigated area recently modernized in northeast Spain) usable in soil water models for the evaluation of the new irrigation system.The recent soil map of the VID (presented in a companion paper) gathered the hydrologic and salinity properties of the horizons in the described soil units. The homogeneous hydrologic zones defined in VID may be used to recommend specific irrigation practices and as the basis for the application of distributed soil water movement models. These hydrologic properties may be applied directly as inputs to the models while the PTFs may allow for setting adequate parameters in nearby areas with similar soils from more readily available soil information (texture, organic matter and gypsum).